2014
DOI: 10.1111/tid.12192
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of long‐term and short‐term administration of itraconazole for primary antifungal prophylaxis in recipients of allogeneic hematopoietic stem cell transplantation: a multicenter, randomized, open‐label trial

Abstract: Long-term and short-term administration of ITCZ both seemed effective in preventing IFD in recipients of allo-HSCT. Further study with large sample size should be performed to evaluate this result. ITCZ shows the same pharmacokinetics in recipients of allo-HSCT as in non-recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Of these 29 studies, seven studies used itraconazole for treatment 30 , 46 51 and 22 studies used itraconazole for prophylaxis. 16 19 , 22 24 , 52 – 65 Fourteen were conducted in European countries, six were in Japan, 16 , 48 , 50 , 53 , 55 , 63 three were in China, 61 , 64 , 65 three were in America, 23 , 57 , 59 two in Australia, 18 , 62 and one in South Korea. 20 Among these, two studies were conducted in children who used itraconazole for prophylaxis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these 29 studies, seven studies used itraconazole for treatment 30 , 46 51 and 22 studies used itraconazole for prophylaxis. 16 19 , 22 24 , 52 – 65 Fourteen were conducted in European countries, six were in Japan, 16 , 48 , 50 , 53 , 55 , 63 three were in China, 61 , 64 , 65 three were in America, 23 , 57 , 59 two in Australia, 18 , 62 and one in South Korea. 20 Among these, two studies were conducted in children who used itraconazole for prophylaxis.…”
Section: Resultsmentioning
confidence: 99%
“… 17 Glasmacher et al, 60 in their study, claimed that there were no severe adverse effects (necessitating an interruption of prophylaxis) clearly attributable to itraconazole, especially no severe hepatotoxicity events. Lin et al’s study 61 showed that drug-related adverse events occurred in 19 (15.7%) of the patients involved, including 15 with gastrointestinal disorders (12.4%), two with abnormal liver function (1.65%), one with hypokalemia (1/121), and one with hydrothorax (0.8%). In Liu’s study there were 16 patients who withdrew from the study due to adverse reactions, including three cases of elevated aminotransferase.…”
Section: Resultsmentioning
confidence: 99%
“…The only new data supporting the use of intravenous itraconazole or its solution are from a few cohort studies reporting IFD rates of 1-7% for HSCT patients and 5% for patients with AML. 53,57,58…”
Section: Voriconazolementioning
confidence: 99%